Scheduling and Control of Parts in FMS industry - Yedukondalu, G; Thakare, Mayur.; Anvesh, V; Hokesh Reddy, R; Cheetri, Akin (International Journal of Engineering and Technology, 2018)
This paper introduces scheduling of parts in Flexible Manufacturing System (FMS) environment by means of discrete-event simulation method. Modeling of FMS layout with 3 distinct part type, route and interval for each part is developed using Arena simulation. The ranking criterion is considered only for First-in-first-out (FIFO). Automatic Guided Vehicles (AGV) is used as a Material Handling System (MTH). In this paper a case study has been presented for effective utilization of machines and AGV in given FMS. Based on processing time for variety of parts according to their route priority the jobs are scheduled. The scheduling of the considered layout are evaluated and compared to 6 output measures which are avg. work in process (WIP), avg. queue time, avg. number of parts waiting, resource seized, machine instantaneous utilization and scheduled utilization for different replication length. The simulation outcomes are discussed in detail and conclusion has been drawn for various mentioned output measures.Â